Prognostic value of oxygen inhalation therapy for simple nocturnal hypoxemia in COPD: a meta-analysis - Sun, Ling; Chang, Ya-Fei; Wang, Yun-Fei; Ran, Xian-Zhong; Li, Xiang-Rong; Xie, Quan-Xin; Ning, Bin (Frontiers in Pharmacology, 2023)
The effect of oxygen therapy on the prognosis of chronic obstructive pulmonary disease (COPD) with nocturnal hypoxemia (NOD) has been controversial.Therefore, this study systematically evaluated the relevant literature and included it into randomized controlled studies for meta-analysis to evaluate the efficacy and prognosis. Methods: We searched PubMed, EMBASE, web of science, Cochrane, China HowNet and Wanfang database for the literature on the prognosis of COPD patients with simple nod from the establishment of the database to June 30, 2022. The outcome indicators were death and aggravation of the disease. The efficacy evaluation measures were pulmonary function and arterial blood gas results. The publication bias and heterogeneity of the included studies were evaluated. Results: A total of 621 patients from 5 studies were included in this meta-analysis, and there was no publication bias in the included studies. The total mortality of long-term oxygen therapy (LTOT) in COPD patients with simple nod in oxygen therapy group (RR = 1.04; 95% CI: 0.82-1.34, P = 0.73), mortality (RR = 0.85; 95% CI: 0.62-1.16, P = 0.31), risk of progression to LTOT events (RR = 1.07; 95% CI: 0.76-1.51, P = 0.68).PaO2 in patients with COPD and simple nod in oxygen therapy group was higher than that in non-oxygen therapy group (mean difference (MD) = 13.47; 95% CI: 3.49-23.46, P = 0.0008), the decrease of PaCO2 level was not statistically significant (MD = -10.05; 95% CI：-26.36-6.27，P = 0.23). Conclusion: Oxygen therapy can improve the prognosis of blood oxygen partial pressure in COPD patients with simple nod, but oxygen therapy has no significant effect on the survival rate, controlling the progression of the disease to LTOT and reducing the partial pressure of carbon dioxide.